Extravascular complications following abdominal organ transplantation. Issue 8 (August 2015) - Low, G.; Jaremko, J.L.; Lomas, D.J.
<x xml:space="preserve">Abstract</x> A variety of transplants have been performed in the abdomen including liver, kidney, pancreas and islet, bowel, and multivisceral transplants. Imaging plays an important role in graft surveillance particularly to exclude post-transplant complications. When complications occur, therapeutic image-guided interventions are invaluable as these may be graft-saving and even life-saving. Vascular complications following transplantation have been extensively reported in recent reviews. The focus of this review is to discuss post-transplant complications that are primarily extravascular in location. This includes biliary, urological, intestinal, malignancy, infections, and miscellaneous complications. Familiarity with the imaging appearances of these complications is helpful for radiologists as accurate diagnosis and expedient treatment has an impact on graft and patient survival.